2018
DOI: 10.2196/10515
|View full text |Cite
|
Sign up to set email alerts
|

Development and Management of Networks of Care at the End of Life (the REDCUIDA Intervention): Protocol for a Nonrandomized Controlled Trial

Abstract: BackgroundEnd-of-life needs can be only partly met by formalized health and palliative care resources. This creates the opportunity for the social support network of family and community to play a crucial role in this stage of life. Compassionate communities can be the missing piece to a complete care model at the end of life.ObjectiveThe main objective of this study is to evaluate the REDCUIDA (Redes de Cuidados or Network of Care) intervention for the development and management of networks of care around peo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The increase in these care networks improves the quality of life of the person, reduces the burden of the main caregiver and improves the satisfaction of patients and their families. These results are already being analyzed in a community intervention process through the RedCuida protocol for the creation and management of care networks [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in these care networks improves the quality of life of the person, reduces the burden of the main caregiver and improves the satisfaction of patients and their families. These results are already being analyzed in a community intervention process through the RedCuida protocol for the creation and management of care networks [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Of 35 studies, we identified five (14%) that specifically measured a health system outcome (Table 2) in a public health palliative care context, [36][37][38][39][40] including three studies examining this outcome as a primary endpoint. 36,37,39 The quality of these studies was classified as high, with scores ranging from 31 to 36. Two studies identified were trial design papers outlining protocols for work currently being undertaken, 37,38 meaning evidence on health service use outcomes from public health approaches was limited to the findings of three studies.…”
Section: Evidence For Health System Impactmentioning
confidence: 99%
“…40 These studies typically involved cohorts of selected 'patients' who were seriously ill, frail, or with clinically identified vulnerabilities. This ranged from broadly people with advanced disease 37,38 including specifically advanced cancer 39 expected to be at 37 or within their last year of life, 38,40 and/or in addition: those screened as dependent for basic and instrumental daily activities (Barthel Activities of Daily Living Index Scale <3), with more than 40% of their needs unmet by community, and experiencing loneliness (ESTE score > 20 points) with a caregiver experiencing burden (Zarit Cale > 56); 37 those with unmet social and/or practical needs who are socially isolated or dependent upon just one other person to meet their needs and at having least two indicators of deteriorating health as outlined in the Supportive & Palliative Care Indicators Tool (SPICTTM) 38 ; patients clinically identified at risk of unplanned admission. 36 The commonality across the public health palliative care approaches described was the systematic leveraging of enhanced community networks of care by a centrally coordinated programme which sought to aid the person with serious illness through the linkage to and bolstering of regionally based resources.…”
Section: Evidence For Health System Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…changes in the patients' quality of life when involving volunteers; evaluation of a model to develop networks of care around people) instead of on the project as a whole. [15][16][17][18] Publishing study protocols of studies, including both process and outcome evaluations, helps in better understanding the development, implementation and outcomes of Compassionate Cities.…”
mentioning
confidence: 99%